The Impact of Communication on Employee Performance: Evidence from the Department of Culture, Youth, Sports, and Tourism of Surabaya City - Hosniawati; Kurniawan, Gogi; Hafidulloh (UMSurabaya Publishing, 2025)
Abstract: Effective communication is a critical determinant of performance in public institutions with complex, multidimensional functions. This study investigates the effect of communication on employee performance at the Department of Culture, Youth, Sports, and Tourism of Surabaya City. Employing a quantitative, explanatory research design, data were collected from all 53 employees using a Likert-scale questionnaire and analyzed with SPSS, incorporating validity and reliability tests, simple linear regression, and hypothesis testing. The results indicate that communication exerts a strong, positive, and significant influence on employee performance (β = 0.820, R² = 0.672), with goal setting, instruction delivery, and reporting emerging as the strongest indicators. Conversely, feedback provision and complaint handling remain areas for improvement. The findings underscore the need for strengthening two-way communication, institutionalizing constructive feedback mechanisms, and fostering a participatory work climate to optimize employee performance. Keywords: Communication, Employee Performance, Public Sector